2016
DOI: 10.1155/2016/7179028
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Peritonitis in a Pediatric Dialysis Program in Guatemala, 2011–2014

Abstract: Background. Peritonitis is the most common complication of peritoneal dialysis but there is limited data regarding peritonitis related risk factors in developing countries. Objective. Describe the PD program at Foundation for Children with Kidney Disease (FUNDANIER), in Guatemala, and identify peritonitis related risk factors in these patients. Methods. This retrospective open cohort study included medical records from FUNDANIER during 2011 to 2014. Baseline demographics, treatment modalities, caregivers' char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A high school/technical degree in Guatemala represents a relatively high level of education and characterizes the environment surrounding the child, and may even shed light on the socio-economic situation of the household. When the mother is also the caretaker of the child (as is the case for 72% of participants in this study), her educational level also serves as a proxy for the level of care a patient receives in the household [ 35 ]. The mother’s educational level in this study may reflect a household environment that may enhance the mother’s capacity to manage their child’s disease, either as a direct caretaker, or as a contributor to the household, or both.…”
Section: Discussionmentioning
confidence: 99%
“…A high school/technical degree in Guatemala represents a relatively high level of education and characterizes the environment surrounding the child, and may even shed light on the socio-economic situation of the household. When the mother is also the caretaker of the child (as is the case for 72% of participants in this study), her educational level also serves as a proxy for the level of care a patient receives in the household [ 35 ]. The mother’s educational level in this study may reflect a household environment that may enhance the mother’s capacity to manage their child’s disease, either as a direct caretaker, or as a contributor to the household, or both.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of peritonitis decreased in both adult and children over the past several decades [26][27][28][29][30]. In this study, 52% of the patients had at least one episode of peritonitis with a rate of peritonitis being 1 episode per 22 patient-months [20,23,31]. This is considered to be low rate in comparison to others: one episode of peritonitis every 4.3-18 patient-months [32][33][34].…”
Section: Discussionmentioning
confidence: 77%
“…A study from Saudi Arabia [22] reported that the mean age was 7.3 years, but the mean duration of peritoneal dialysis was less than what we found in this study which could be explained by the shortage of available kidneys for transplant in Jordan. The median duration on PD was high in the hospital compared to others [23] because most of the children were below 5 years and due to the paucity of available kidneys for transplant.…”
Section: Discussionmentioning
confidence: 94%
“…Providing services such as water, electricity, and toilet at houses are important for performing peritoneal dialysis in clean conditions. In an important study on this subject, it has been shown that the rate of peritonitis is higher in those whose housing conditions are not good [18]. Although there is frequent power outage in the houses of our patients living in the rural, all of our patients had access to services such as water and electricity.…”
Section: Discussionmentioning
confidence: 91%